Effects of dietary oil palm carotenes on colour intensity and astaxanthin content in giant freshwater prawn (Macrobrachium rosenbergii) - Md Noh Abidah,; Wan Nooraida Wan Mohamed,; Nur Atikah Ibrahim,; Saminathan Mookiah,; Muhammad Amirul Asraf Fuat, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Prawns have the metabolic ability to convert dietary carotenoids, such as beta-carotene, into astaxanthin, which increases the colour intensity and boosts immunity, thereby improving prawn growth performance. Currently, prawn feed manufacturers are using expensive synthetic astaxanthin as a feed supplement, which leads to higher feed costs. Oil palm carotene can be used in prawn feed production to replace the commercial synthetic astaxanthin in the market. A study was conducted to evaluate the effects of dietary oil palm carotene on the colour intensity, total carotenoids, and astaxanthin content of giant freshwater prawns (Macrobrachium rosenbergii). Five different treatments that are isonitrogenous and isocaloric were used in this study, including T1 (commercial feed); T2 (control, without oil palm carotene); T3 (3% crude palm oil (CPO) inclusion); T4 (3% palm pressed fibre oil (PPFO) inclusion); and T5 (3% commercial oil palm-mixed carotene inclusion). Prawns were fed to satiation five times daily during the 10-week feeding trial. At the end of the feeding trial, prawn samples were collected for colour intensity, total carotenoids, and astaxanthin content analysis. The T4 and T5 prawn samples showed better colour intensity in terms of lightness in cooked samples as well as yellowness and redness for both raw and cooked samples. Prawns fed with diets consisting of oil palm carotenes (T3, T4 & T5) contained higher total carotenoids content (more than 40 ppm) and astaxanthin content (ranging from 14.65 to 16.96 ppm) than the commercial (T1) and control (T2) groups. These results indicate that supplementation of oil palm carotenes in the giant freshwater prawn can potentially replace expensive commercial synthetic astaxanthin that is practically used by aquaculture feed producers.